The Fermentation Study on Polyhydroxyalkanoates Produced by Ralstonia eutropha from Hydrolized Sago Starch as The Carbon Source - Atifah, Nur; Syamsu, Khaswar; Suryani, Ani (Jurnal Teknologi Pertanian, 2007)
Polyhydroxyalkanoates (PHAs), microbial bioplastics, not only were similar in properties with those made of petrochemical products, they were also completely biodegradable. At the moment, the price of PHAs was still high. This research was conducted to investigate the ability of Ralstonia eutropha to produce PHAs on a sago starch-based substrate, one of the cheap and abundantly renewable resources in Indonesia, and to characterize the PHAs produced. The microorganism was grown on the hydrolyzed sago starch with an initial sugar concentration of 30 g/lIt was found that the best value of the maximum specific growth rate (µmax) was  0,188 h-1. Kinetic parameters at 96 hour-batch fermentation showed the respective final cell and PHA concentrations of 4,41 g/L and 1,44 g/L. The yields of cell biomass (Yx/s), PHAs per gram of cells (Yp/x), PHAs per gram of substrate (Yp/s) and the percentage of substrate consumption  (∆S/So) were, 0.15 g cell/g sugar; 0.35 g PHA/g cells; 0.06 g PHA/g sugar and 99%, respectively.  The PHAs produced were predominantly composed of poly(3-hydroxybutyrate) (PHB) as the functional groups with a melting point of 163,96 oC.Keywords : hydrolyzed sago starch, PHA, Ralstonia eutropha